Manajemen Pembelajaran dalam Meningkatkan Mutu Pendidikan Di MI Takhassus Tahfidzul Qur’an Prapagkidul, Pituruh, Purworejo - Nastangin Nastangin (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2019)
This research is based on the importance of learning management in improving the quality of education. In this regard, this study aims to determine learning management in improving the quality of education at MI Takhassus Tahfidzul Qur'an Prapagkidul, Pituruh, Purworejo. This research is a qualitative research. Data collection uses interviews, observation, and documentation, and data validity uses triangulation, and data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. This study resulted in the following conclusions. (1) Learning planning at MI Takhassus Tahfidzul Qur'an Prapagkidul is formulated at the beginning of the school year by involving all management components (school committee, principal, teachers and employees) as a form of service for their presence in the madrasah; (2) Implementation of learning at MI Takhassus Tahfidzul Qur'an Prapagkidul applies a class teacher system and a system of study teachers (religious subjects, sports, tahfidz, English, abacus and cultural arts), while the methods used in the teaching and learning process include lecture method, question and answer method, discussion method, demonstration method, experimental method, assignment, direct practice and simulation adapted to the material being taught. The learning method was developed into a value-oriented (affective) teaching technique; (3) Supervision of learning at MI Takhassus Tahfidzul Qur'an Prapagkidul is carried out by the Head of the Madrasah to classes, the time is conditional for Mr or Mrs Teacher evenly from class 1 to class VI. Internal supervision of the implementation of the madrasah work program and evaluation which is carried out openly. The involvement of all components in the monitoring and evaluation of work programs has been proven capable of producing maximum performance for all components of the school; (4) Learning evaluation at MI Takhassus Tahfidzul Qur'an Prapagkidul is carried out after the learning activities are completed, with the aim of tracing, checking, searching and concluding the implementation includes cognitive aspects, affective aspects and psychomotor aspects and aspects of student behavior and not only assesses theoretically but practice. The forms of assessment are written tests, oral tests and practical tests, assignments, quizzes, group or individual work, assessment of work, assessment of student attitudes and behavior. The forms of test instruments that are often used are multiple choice, short answer descriptions and portfolios; (5) Learning reporting at MI Takhassus Prapagkidul is done as a form of personal and educational institution responsibility and commitment. The forms of reporting at MI Takhassus Tahfidzul Qur'an Prapagkidul are as follows: (a) Assessment reports by educators; (b) Assessment reporting by educational units; (c) Reporting of assessments by the government.